2016
DOI: 10.1089/neu.2015.4191
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Changes in Peripheral Gene Expression following Sports-Related Concussion

Abstract: We conducted a prospective study to identify genome-wide changes in peripheral gene expression before and after sports-related concussion (SRC). A total of 253 collegiate contact athletes underwent collection of peripheral blood mononuclear cells (PBMCs) before the sport season (baseline). Sixteen athletes who subsequently developed an SRC, along with 16 non-concussed teammate controls, underwent repeat collection of PBMCs within 6 h of injury (acutely). Concussed athletes underwent additional sample collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 56 publications
(57 reference statements)
9
44
1
Order By: Relevance
“…In view of the latter, injury-induced alterations to hormones produced by both the sympathetic nervous system and hypothalamic-pituitary-adrenal (HPA)-axis can modulate peripheral immune function, altering blood levels of cytokines and chemokines (58)(59)(60). While we did not find differences in blood concentrations of the inflammatory chemokine MCP-1 between concussed and healthy athletes in either the subacute period or at medical clearance, MerchantBorna et al observed that at 7 days after SRC, gene transcription profiles in peripheral blood leukocytes were perturbed, reflecting potential dysregulation of the HPA-axis (25). In addition, we recently demonstrated that acutely elevated levels of peripheral catecholamines after moderate and severe TBI were highly correlated with elevated circulating concentrations of inflammatory cytokines and chemokines (19).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In view of the latter, injury-induced alterations to hormones produced by both the sympathetic nervous system and hypothalamic-pituitary-adrenal (HPA)-axis can modulate peripheral immune function, altering blood levels of cytokines and chemokines (58)(59)(60). While we did not find differences in blood concentrations of the inflammatory chemokine MCP-1 between concussed and healthy athletes in either the subacute period or at medical clearance, MerchantBorna et al observed that at 7 days after SRC, gene transcription profiles in peripheral blood leukocytes were perturbed, reflecting potential dysregulation of the HPA-axis (25). In addition, we recently demonstrated that acutely elevated levels of peripheral catecholamines after moderate and severe TBI were highly correlated with elevated circulating concentrations of inflammatory cytokines and chemokines (19).…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, alterations in various circulating indices of brain tissue damage such as glial fibrillary acidic protein (GFAP), s100 calcium-binding protein B (s100B), neuron specific enolase (NSE), αII-spectrin N-terminal fragment (SNTF) (22)(23)(24), and inflammatory genes (25,26) have been observed in the acute and subacute phases after SRC.…”
Section: Introductionmentioning
confidence: 99%
“…8 In sports-related mTBI an immediate activation of the innate immune system (interleukin 6 , IL-12) has been observed with return to baseline after a week. 9 The long-term course of systemic inflammation and type of cytokines present in blood in patients with mTBI has been evaluated sparsely, with one study including 52 patients showing an increase of IL-1b, IL-6, and monocyte chemoattractant protein 1 (MCP-1) over a 3-month period with association of MCP-1 to postconcussion syndrome. 10 Many patients with mild TBI are not admitted to hospitals and are thus possibly underrepresented in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Differential gene expression is reported in a small number of clinical TBI studies (7)(8)(9)(10), with few studies relevant to blast TBI (11)(12)(13). Gene expression regulation is imperative to appropriate cellular response to external mechanical, environmental, or biological stimuli, and the nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) complex is a main transcription factor of these adaptive gene expression changes (14).…”
Section: Introductionmentioning
confidence: 99%
“…Within clinical studies of TBI, changes in the NF-κB network are reported in a limited number of studies (7)(8)(9)(10); however, they have not yet been examined in biTBI. Preclinical studies of blast exposures have demonstrated altered gene expression, including cognitive impairment (20,21) and immune function (22).…”
Section: Introductionmentioning
confidence: 99%